Clinical outcomes after implantation of a toric intraocular lens with a transitional conic toric surface - Thomas, Bettina C.; Khoramnia, Ramin; Auffarth, Gerd U.; Holzer, Mike P. (British journal of ophthalmology, 2018)
Purpose: To evaluate the postoperative outcomes after implantation of a hydrophilic toric intraocular lens (tIOL) with a transitional conic toric surface in patients with astigmatism undergoing refractive lens exchange (RLE) or cataract surgery. Methods: In this monocentric study, clinical outcomes following implantation of the hydrophilic Precizon toric IOL model 565 (Ophtec) were analysed. For intraoperative axis alignment, the Verion Image Guided System was used. Intended versus achieved refraction, IOL position, visual acuity outcomes and power vector analyses were evaluated 3 months postoperatively. Results: Forty-three eyes of 28 patients (40 eyes cataract, 3 eyes RLE) received a Precizon toric IOL with a cylindrical power between 1.0 and 7.5 D. Target refraction was emmetropia except for four eyes that had a myopic target. The median postoperative IOL rotation at slit lamp was 3° with a range from 0° to 16°. Uncorrected distance visual acuity (UDVA) increased from median 0.5 logMAR preoperatively to median 0.06 logMAR at 3 months postoperatively. Corrected distance visual acuity increased from 0.20 to −0.02 logMAR. Median preoperative subjective cylinder was 1.5 D and 3 months postoperatively 0.25 D. Conclusion: Preoperative diagnostics, IOL selection and correct intraoperative positioning of tIOLs are essential for good outcomes and postoperative spectacle independence following cataract or RLE surgery. Visual acuities and rotational stability of the Precizon toric IOL showed very good outcomes and the subjective postoperative astigmatism could be reduced significantly.